PROJECT: SCREENPLAY METAMORPHOSIS - Fransisca Vinybelinda; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This paper explains the processes and the result of my final project in a form of screenplay entitled Metamorphosis. The screenplay is a story of a man, Johan Tanuwijaya who transforms from a psychologically sound man to a psychologically disturbed man. To develop my story, I used trauma as one of the themes and the theories. At first, he experienced traumatic childhood, then he recovered until his adulthood and marriage life, where he married his dire attention-seeker wife, Renata. Slowly, he was thrown back to his childhood trauma and that drove him insane. Eventually, he killed his wife and he created another himself in his daughter. From this screenplay I expect that people will have new principles and views about domestic violence and abuse, so that Indonesian society will have improvements in the future